Social communications of students in the modern intercultural space - Kuzmenko, Taras; Tsoi, Tetiana; Goncharenko, Iuliana; Zhvania, Liudmyla (Editorial Authors and Associated Researchers (EAAR), 2021)
The aim of this article is to study the influence of social communications on the formation of relations between students in the intercultural space on the example of the State Higher Educational Institution "Vasyl Stefanyk Precarpathian National University" and Kyiv University named after Borys Hrinchenko. Methods: analysis, synthesis, abstraction, modeling, description, observation, comparison, tabular and graphical representation, questionnaires and generalizations. Results: It is determined that countries such as Australia, Canada, Great Britain, New Zealand, France and the Netherlands have the highest rates of attracting foreign students to study in higher education institutions. The most international universities in the world are the University of Hong Kong, ETH Zurich, Chinese University of Hong Kong, University of Oxford and Imperial College London, which occupy the first five positions in the World University Rankings 2021. It was found that most often social communication between students belonging to different socio-cultural groups occurs using social media.
Keywords: internationalization; social media; higher education institution; communication; international group